Comparative Study of Public Services in Pangalengan and Coblong Districts - Nadya Tania Lisnawati; Fadiya Nabila Putri; Viola Vera Levina; Andre Ariesmansyah; Siti Sa’adah (CV. Rayyan Dwi Bharata, 2023)
Public services are all activities in the framework of fulfilling basic needs in accordance with the basic rights of every citizen and resident over goods, services and or administrative services provided by service providers related to public interests. Communities as customers have needs and expectations for the performance of professional public service providers. The task of the Central Government and Regional Governments is to provide public services that are able to satisfy the public. The implementation of decentralization and regional autonomy policies in Indonesia has resulted in local governments having the responsibility and authority to determine minimum service standards. The fundamental problem in the process of public service in Indonesia is about ethics. There are no universal standards regarding norms or ethics as well as sanctions that specifically regulate violations committed by officials in public services.